Edukasi Kesehatan Mental untuk Pencegahan Gangguan Psikologis pada Remaja di SMK Kesehatan Pro-Skill Indonesia, Pekanbaru - Ikhsan Nursyafik; Nichita Khairun Nisya; Chica Zahwa Naira Melani Ginting; Nesaliya Azhari; Rusda Aulia; Kiki Zein Yulivia; Syahwa Elmina Safitri; Yogi Candra; Rafinda Rafinda; M. Rusydy (CV. IRA PUBLISHING, 2026)
Mental health education was conducted at SMK Kesehatan Pro‑Skill Indonesia, Pekanbaru, with the aim of increasing knowledge, awareness, and coping skills among adolescents as an effort to prevent psychological disorders. As many as 150 tenth-grade students participated in the activity on May 08, 2026. The intervention took the form of a counseling session titled